Decolonial Daydreams │Taba Aiboli An exploration of the construction of female power Amongst the Lozi people - Matakala, Chaze (African Studies, 2021)
This thesis offers an exploration of the construction of female power amongst the Lozi people of the western province of Zambia, also known as Barotseland. Colonial empirical texts, contemporary literature on Lozi social history, heritage and public culture gloss over the matriarchal roots of Lozi society, leading to the collective, individual and intellectual imperative of this study. Insights necessary for engagement point to the dynamic role of gender in the origin, enactment and preservation of the Lozi royal kinship structure. Building on existing work on the origins of the Lozi royal kinship and the shifts of power through the (post)colonial political periods, the main objective of this research project is to conduct qualitative research into the dynamic role of gender in Lozi society. Data was based on a review of literature on the Lozi people and semi-structured interviews with nine Key Informants in Barotseland who bear embodied knowledge on the ideology of the Lozi royal kinship structure and the sociocultural systems apparent in Lozi society. A qualitative thematic network data analysis demonstrated political motherhood as a mechanism to act as a balancing check on the patrilineal system. The cross-cutting theme of political motherhood across generations and gender is manifested in the roles of Natamoyo and Mukwae Ngula, who are the respective male and female Ministers of Justice. In addition to these roles which emerge from an operative ethic of communalism are the council of women known as Anatambumu. The findings of this research indicate that there are cohesive interacting sociocultural systems that are focused on the mother figure (matrifocal) and also endorsing descent through the male line (patrilineal). Moreover, analysis of the responses shows that there is a strong correlation between the physical geography of Barotseland and the divine ancestresses, Mbuyu and her mother Mwambwa. On this basis it is recommend that the effects of the integration of Barotseland into the postcolonial state of Zambia be studied further, especially as it pertains to political motherhood, marriage and systems of descent amongst the Lozi.